The Effect of Wages and Incentives on Employee Performance Improvement - Norbaiti Norbaiti; Hamdilah Hamdilah; Nirza Marzuki Husein; Zainal Arifin (STKIP Singkawang, 2022)
This study aims to analyze the effect of wages and incentives on employee performance. This research was also causal associative, namely research that aims to determine the causal correlation between two or more variables, namely the independent or independent variables (wages and incentives) on the dependent variable (employee performance), with the respondents as private employees who had various positions in private companies in Banjarmasin as many as 30 people. Questionnaires were divided, tabulated, and tested with correlation regression to determine the relationship between variables. The results showed that partially wages had a significant positive effect on increasing employee performance, partially giving incentives had a significant positive effect on increasing employee performance, and simultaneously wages and incentives had a significant positive effect on increasing employee performance.